Internalization Values of Religious Moderation Using Theoanthropoecocentric Pradigma at Ma'had Al-Jamiah at IAIN Padangsidimpuan - Hamdan Hasibuan; Irsal Amin; Achmad Yani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The presence of Ma'had Al-Jamiah at an Islamic religious college must be a laboratory for internalizing the values of religious moderation. The internalization process must run in line with the social demands of society through higher education institutions. This research was field research with a qualitative descriptive type, namely to reveal the process of internalizing the values of religious moderation to students at Ma'had al-Jamiah IAIN Padangsidimpuan. Collecting data used observation techniques, interviews, and documentation. Meanwhile, to analyze the data used triangulation, namely collecting data and classifying, presenting, and drawing conclusions. The results showed that the process of internalizing the values of religious moderation using the theoanthropoecocentric approach (divinity, humanity, and the environment) was carried out with a learning process that was programmed into several parts, namely strengthening divine values compared to fiqh values that vulnerable to differences, prioritizing the concept of humane life through a pattern of living in a dormitory with values of harmony, togetherness, mutual respect for differences in understanding in religion, and creating an attitude of loving the environment. These three aspects are mutually reinforcing because they have a very close relationship. This study concludes that students who understand the true faith have a tolerant human attitude, and would appreciate God's creation in the form of the universe. Keywords: Internlization Religius Value, Theoanthropoecocentric Pradigma, Religious Moderation Value